Parental divorce and its effects on the psychological well-being of children - Orcullo, Daisy Jihan; Ismail, Nik Ahmad Hisham (Institut Terjemahan dan Buku Malaysia, 2016)
The study on the internalising effects and externalising effects of parental divorce on the well-being of children. Discussions on gender differences and psychological experiences of children toward divorced parents.